PENGARUH LINGKUNGAN KERJA, BEBAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PT BIRMA GEMILANG PRIMA JAKARTA UTARA - Salsabila Putri Ayu Chairunnisa (2022)
This study is a quantitative examination led with the reason to be aware and demonstrate the impact of the workplace, workload, and work stress on turnover intention. The study object is the workers of PT Birma Gemilang Prima North Jakarta. This research used 33 respondents. The sampling strategy used in this research was a saturated sample technique. The hypothesis in this research to see impact either partially and simultaneously of the variables X and Y, so therefore test used are the coefficient of determination test, t test and f test. The analysis in this study used SmartPLS 3.0. The research results obtained are: (1) work environment has a positive and significant effect on turnover intention, (2) workload has a negative and significant effect on turnover intention, (3) work stress has a positive and significant effect on turnover intention, (4) work environment, workload, and work stress has a significant effect on employee turnover intention at PT Birma Gemilang Prima North Jakarta.